PERANCANGAN SENSOR KADAR OKSIGEN UNTUK IDENTIFIKASI PENDERITA STROKE DENGAN METODE NON INVASIVE - Brama Sakti Handoko; Suryani Alifah; Arief Marwanto (Elkom : Jurnal Elektronika dan Komputer, 2022)
Stroke is the number one cause of disability and the second cause of death in the world. Blood flow that is not smooth in stroke patients causes hemodynamic disorders including changes in the value of oxygen saturation in the blood (SpO2) which can interfere with the function of internal organs including the heart due to lack of oxygen intake. So we need a system to monitor the oxygen saturation value which can be used as an early indicator in recognizing stroke patients. This system uses detection of two sensors to measure oxygen saturation in the blood, a microcontroller to process data, a monitor to display data, a buzzer as a warning of the lower limit of measurement and a micro sd card module to store measurement data that has been running. Parameters displayed include the date of measurement, patient ID, SpO2-1, SpO2-2, last SpO2-1 and last SpO2-2. This system will measure and display the SpO2 value of both right and left arms simultaneously. Stroke patients who experience muscle weakness in one hand may experience different values with a hand that does not experience muscle weakness. This study aims to develop an SpO2 monitoring system that will be used to detect stroke patients with non-invasive methods. The results show that the system has been developed and can be used to measure the patient's SpO2 from both hands simultaneously with a measurement error rate of ±2% for each sensor from standard medical equipment.